Effect of Venting on the Explosion of Aluminium-Silver Powder Mixtures - Khairiah Mohd Mokhtar; Che Rosmani Che Hassan; Rafiziana Md Kasmani; Mahar Diana Hamid; Mohamad Iskandr Mohamad Nor; Mohd Usman Mohd Junaidi (ASEAN Journal of Chemical Engineering, 2020)
Dust explosion is considered as a serious threat for the industry that use or handle combustible materials as it may lead towards a significant economic loss in terms of damage to the facilities and suspension of activities, severe workplace injuries and fatalities. The rapid pressure developed during a dust explosion can be mitigated by venting. The present work explored the effects of venting on the explosion of different mixing weight ratios of aluminium and silver powder mixtures. The explosion characteristics of aluminium-silver mixtures were assessed in a 0.0012 m3 confined and vented cylindrical vessel. It was found that the application of 0.1 bar static burst pressure (Pstat) venting membrane gives one tenth reduction on explosion pressure and maximum rate of pressure rise for 70:30 and 50:50 mixing weight ratios of aluminium-silver mixtures explosion, respectively. This finding suggests that besides the venting application effect, the oxidation reaction of aluminium could be disrupted due to the presence of silver powder in the metal mixtures which results in lower heat transfer and reduction of the mass burning rate, hence, lessen flame speeds and explosion severity. However, the venting effectiveness is reduced when the Pstat increases. In order to assess the applicability of the dust explosion venting standard; NFPA 68 and EN 14491, the experimental results were compared with the calculated values according to the standards. The comparative results show that, both NFPA 68 and EN 14491 give underestimated values for explosion venting as compared with the experimental results.